The gendered crisis: Livelihoods and mental well-being in India during COVID-19 - Farzana Afridi; Amrita Dhillon; Sanchari Roy (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2021)
This paper studies the impact of the COVID-19 crisis on the gendered dimensions of employment and mental health among urban informal-sector workers in India. First, we find that men's employment declined by 84 percentage points post-pandemic relative to pre-pandemic, while their monthly earnings fell by 89 per cent relative to the baseline mean. In contrast, women did not experience any significant impact on employment post pandemic, as reported by their husbands. Second, we document very high levels of pandemic-induced mental stress, with wives reporting greater stress than husbands. Third, this gendered pattern in pandemic-induced mental stress is partly explained by men's employment losses, which affected wives more than husbands. In contrast, staying employed during the pandemic is associated with worse mental health for women and their (unemployed) husbands. Fourth, pre-existing social networks are associated with higher mental stress for women relative to men, possibly due to the 'home-based' nature of women's networks.
Keywords: J16; J22; J23; O14; 330; COVID-19; informal sector; employment; mental health; social networks; gender; India